Long‐term effects of the nine‐item list intervention on obstetric and neonatal outcomes in Robson group 1 – A time series study. (1st September 2020) - Hildebrand, Eric; Nelson, Marie; Blomberg, Marie
Abstract: Introduction: The nine‐item list, with organizational and cultural changes, was implemented at the delivery unit in Linköping, Sweden between 2007 and 2010, aiming at improving the quality of care by offering more women a safe and attractive vaginal delivery. The target group for the intervention was nulliparous women at term with spontaneous onset of labor and cephalic presentation (Robson group 1). The aim of this study was to evaluate pregnancy outcomes before, during, early post and late post introduction of the nine‐item list. Material and methods: Robson group 1 births (n = 12 763) from 2004 to 2018 were divided into four time periods; before the nine‐item list (2004‐2006), during introduction of the nine‐item list (2007‐2010), early post introduction of the nine‐item list (2011‐2014) and late post introduction of the nine‐item list (2015‐2018). The nine‐item list consists of monitoring of obstetric results, midwife coordinator, risk classification of women, three midwife‐competence levels, teamwork—the midwife, obstetrician and nurse working as a team with the common goal of a normal delivery, obstetric morning round, fetal monitoring skills and obstetric skills training. Perinatal outcomes before, during, early post and late post introduction were compared using a Student's t test for numerical variables and a Pearson chi‐squared test for categorical variables. Results: Apgar score <7 at 5 minutes, Apgar score <4 at 5 minutes and umbilical cord arterial pH <7 did not differ significantly between the four time periods. Between before introduction and early post introduction, instrumental vaginal delivery decreased from 19.8% to 12.2% and cesarean section from 9.6% to 4.5%. The late post introduction period showed a maintained effect with 10.7% instrumental deliveries and 3.9% cesarean sections. Obstetric anal sphincter injury grade III decreased instantly during the introduction of the nine‐item list from 7.8% to 5.1% and thereafter remained unchanged. Conclusions: Implementation of the nine‐item list increased the proportion of spontaneous vaginal deliveries by reducing the number of instrumental deliveries and cesarean sections without affecting the neonatal outcomes in nulliparous women with spontaneous onset of labor. The nine‐item list intervention seems to provide long‐term sustainable results.